2 Peter and Jude - Knight, Jonathan (Sheffield, UK Sheffield Academic, 1995)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Peter 2nd -- commentaries; Bible. N.T. Jude -- commentaries